Upaya Teknis Pencegahan Dan Penanggulangan Swabakar (Spontaneous Combustion) Pada Stocpile Di PT. Manambang Muara Enim Kecamatan Lawang Kidul, Kabupaten Muara Enim, Provinsi Sumatra Selatan - Jepriansyah; Hendro Purnomo; Shilvyanora Aprilia Rande (ReTII, 2023)
PT. Manambang Muara Enim is a company engaged in coal mining. The research was conducted at a stockpile location which has a storage capacity of 170,000 tons, and the main problem in stockpiling coal in the stockpile is self-combustion. Piles of coal in self-combustion stockpile will cause losses for the company such as a decrease in coal quality which will affect market demand, wasted part of the coal volume and the company must incur additional costs for handling burning coal. The purpose of this research is to find out the causes of coal self-combustion in the stockpile area and find out how to prevent and control coal self-combustion in the PT.MME stockpile area. The method used in this study is a quantitative method by conducting literature studies to find references related to the research topic, followed by field observations to determine field conditions, then collecting secondary data and primary data, then data processing and data analysis as well as conclusions and suggestion. The cause of self-combustion at PT MME is that the implementation of stockpiling and unloading has not fully implemented the FIFO (First in first out) system, so that the initial stockpile takes longer to stockpile and has the potential to cause self-combustion. Therefore, the application of the FIFO (First in first out) system is expected to avoid coal accumulation that takes too long. Then for prevention that is carried out using the FIFO (Fist In-Fist Out) stockpiling and unloading method, monitoring stockpile temperature, periodic compaction and reducing stockpile height. And for the handling of self-combustion which is implemented at PT.MME this is done by digging coal that has a smoke point using a PC200 Excavator then the coal will be taken and moved to another place around the stockpile then spread, or the old coal is stockpiled in the stockpile as soon as possible in hauling so that the coal buildup is not piled up too long in order to avoid self-combustion. Keywords: Stockpile, Self-combustion, Temperature